1995
DOI: 10.1111/j.1432-1033.1995.873_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of the Dissimilatory Sulfite Reductase from Desulfovibrio Desulfuricans (Essex) and Comparison with the Enzyme from Desulfovibrio Vulgaris (Hildenborough)

Abstract: The dissimilatory sulfite reductase desulfoviridin was purified from the membrane (mSiR) and the soluble fraction (sSiR) of the sulfate-reducing bacterium Desulfovibrio desulfuricans (Essex). Molecular and spectroscopic properties were determined and compared with the properties of the soluble desulfoviridin from Desuljovibrio vulgaris (Hildenboroughj. The enzymes were isolated as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…We detected three subunits, ␣ (49 kDa), ␤ (53 kDa), and ␥ (11 kDa) (Fig. 2), and we interpret the native structure to be ␣ 2 ␤ 2 ␥ n (n Ն 2), as suggested for D. desulfuricans Essex 6 (40). The function of the 11-kDa ␥ subunit that was copurified in most sulfite reductases (36) except that from A. fulgidus (9) is not clear at present.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We detected three subunits, ␣ (49 kDa), ␤ (53 kDa), and ␥ (11 kDa) (Fig. 2), and we interpret the native structure to be ␣ 2 ␤ 2 ␥ n (n Ն 2), as suggested for D. desulfuricans Essex 6 (40). The function of the 11-kDa ␥ subunit that was copurified in most sulfite reductases (36) except that from A. fulgidus (9) is not clear at present.…”
Section: Discussionmentioning
confidence: 93%
“…The function of the 11-kDa ␥ subunit that was copurified in most sulfite reductases (36) except that from A. fulgidus (9) is not clear at present. Whereas Pierik et al reported that the ␥ subunit was tightly associated in the DSR of D. vulgaris (36), it was shown that in D. desulfuricans Essex 6, this subunit can be separated during gel filtration, which indicated a less tight association of DsrC with the ␣ and ␤ subunits in that organism (40). The presence and position of the putative promoter 123 nucleotides upstream of the translational start of the dsrA gene and putative termination sequences downstream of the stop codon of dsrB indicate that dsrA and dsrB constitute a single transcription unit and that the genes are coordinately expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In common with other Dsrs, the enzyme has an a 2 b 2 structure and contains siroheme, nonheme iron, and acid-labile sulfur [36]. An additional protein with an apparent molecular mass of 11 kDa is associated with sulfite reductase from D. vulgaris [38] and Desulfovibrio desulfuricans [39,40]. The function of this so called c subunit is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the organisms that have been studied, the enzyme has been isolated from the soluble fraction. Sulfite reductase from D. desulfuricans was found to be partially membraneassociated after gentle disruption of the cells [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding DsrC (ORF8) was displayed in fosmids ws39f7 and ws7f8. DsrC was proposed to further reduce oxidized sulfur intermediates, such as thiosulfate (48,50). Both DsrC and DsrD are not essentially tightly associated with DsrAB (18,40).…”
Section: Resultsmentioning
confidence: 99%